New challenges for academia-economy collaboration - Zavadskas Е. K.; Valiulis, A. V. (Proceedings of National Aviation University, 2001)
The transition period from plan to market economy requires the adaptation of higher education structure and content to new challenges and needs of developing society. The development problems of the country are inseparably intertwined with the aims of the University. Tremendous changes in economy and society, as an avalanche, has descended upon the university. Many problems now have to be solved by universities: fiindamental and applied research, know-how transfer, technical expertise, adopting of new standards, consulting, training, modern marketing and management, active participation in regional or state activities, etc. The internationalization of university, international mobility, studies of foreign languages and modernization of studies are other internal university tasks. Therefore, there is constant necessity for permanent training, development and renewing of university academic and scientific personnel